Femoral revision in total hip arthroplasty using a cementless modular stem: clinical and radiological results with a 8-year follow-up - Spranz, David Maximilian; Skrobek, David; Randoll, Jannis; Kinkel, Stefan; Merle, Christian; Walker, Tilman; Renkawitz, Tobias; Reiner, Tobias (Archives of orthopaedic and trauma surgery, 2024)
Modular femoral components allow for patient-specific restoration of hip joint geometry and the reconstruction of extensive bone defects in revision total hip arthroplasty (THA); however, potential problems of modular implants such as taper corrosion and the risk of implant fracture continue to be of concern. The aim of the present study was to evaluate the clinical and radiological results of a cementless modular revision stem following revision surgery due to aseptic loosening and periprosthetic fracture and to assess patient-reported outcome measures (PROMs) in these patients at mid-term follow-up.